Factors affecting implementation of interventions for oral health, substance use, smoking and diet for people with severe and multiple disadvantage: a community-based qualitative study in England - Sheena E Ramsay; Richard G Watt; Falko F Sniehotta; Eileen Kaner; Martha Paisi; Neha Jain; Martin Burrows; Emma A Adams; Gillian McLellan; Emma C Joyes; Laura J McGowan; David Landes; et al. (BMJ Publishing Group, 2024)
Background Populations facing severe and multiple disadvantage (SMD), co-occurring homelessness, substance use and repeat offending have high levels of physical and mental ill-health. Poor oral health is one of the most common health problems in this population and is closely linked with substance use, smoking and poor diet. Issues related to the implementation of interventions among SMD populations to address oral health and related health behaviours are poorly understood. This study aimed to understand the factors that affect implementation (relevance of setting, acceptability and adverse effects of interventions) and the sustainability of interventions targeting oral health, substance use, smoking and diet for people experiencing SMD.Methods Between August 2021 and April 2023, interviews and focus group discussions were conducted with two groups of participants: (1) people experiencing SMD in Newcastle Upon Tyne/Gateshead and (2) frontline staff, volunteers, policymakers and commissioners from London, Plymouth and Newcastle Upon Tyne/Gateshead. Information was gathered on factors related to the implementation and acceptability of interventions related to oral health and related behaviours. The data were analysed iteratively using thematic analysis.Results Twenty-eight people experiencing SMD (age range: 27-65 years; 21% females) and 78 service providers, commissioners and policymakers (age range: 28-72 years; 63% females) were interviewed or included in focus groups. The data were organised into three overarching themes: environmental, organisational and interpersonal factors. Environmental factors included funding and integrated services; organisational factors included inclusive services, health promotion, prevention and training healthcare providers; interpersonal factors included the presence of support workers and motivation among service providers.Conclusion The implementation and sustainability of health interventions for people experiencing SMD are influenced by factors across environmental, organisational and interpersonal levels that interact with the inherent challenges of disadvantaged groups. The findings highlight the need for tailoring healthcare interventions according to the needs of people experiencing SMD. Further research on the implementation of diet interventions and co-producing interventions is needed.